2020
DOI: 10.1080/0142159x.2019.1708875
|View full text |Cite
|
Sign up to set email alerts
|

Medical students as feedback assessors in a faculty development program: Implications for the future

Abstract: Medical students as feedback assessors Appendices : Annex 1: Quality of the feedback perceived by students 1. The feedback session was useful 2. I improved my history taking skills 3. I improved my physical examination skills 4. I improved my communication skills 5. The tutor was aware of what I needed to learn 6. The tutor made me feel comfortable and confident 7. The tutor asked me my needs 8. The tutor asked me to evaluate what I did well 9. The tutor asked me to evaluate what I could improve 10. The tutor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to a frequency assessment of the items in the Providing Feedback Guide, most students showed the ability to observe behaviors while giving feedback (see items 1 and 2). Related literature (20, 30,36,37) has also reported that effective feedback should focus on specific behaviors and tasks. The findings presented here are in accord with earlier findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a frequency assessment of the items in the Providing Feedback Guide, most students showed the ability to observe behaviors while giving feedback (see items 1 and 2). Related literature (20, 30,36,37) has also reported that effective feedback should focus on specific behaviors and tasks. The findings presented here are in accord with earlier findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback is effective if it emphasizes the crucial and specific steps of performance in real time (33). It should be clear, focused on specific behaviors and tasks, given just in time, motivating, unbiased, objective, descriptive, supportive, appropriate in amount, goal-oriented, focused on the process, and not critical (20, 25,30,37). Verification and detailed explanation are among the most important features of effective feedback (41).…”
Section: Introductionmentioning
confidence: 99%
“…20 Feedback may come from multiple sources, and prior literature has demonstrated that both learners and supervisors value multisource feedback (MSF) as described in Table 1. 49,52,63,[110][111][112][113][114][115][116][117][118][119] Limited literature supports that MSF may be more helpful for identifying strengths and weaknesses compared to standard assessment methods and may be more likely to result in behavior change. 52,63 Multisource feedback may also be effective in distinguishing between high, intermediate, and low performance in learners.…”
Section: Sources Of Feedback and Personnel Involvedmentioning
confidence: 99%
“…20 Feedback may come from multiple sources, and prior literature has demonstrated that both learners and supervisors value multisource feedback (MSF) as described in Table 1. 49,52,63,[110][111][112][113][114][115][116][117][118][119] Limited literature supports that MSF may be more helpful for identifying strengths and weaknesses compared to standard assessment methods and may be more likely to result in behavior change. 52,63 Multisource feedback may also be effective in distinguishing between high, intermediate, and low performance in learners.…”
Section: Sources Of Feedback and Personnel Involvedmentioning
confidence: 99%